Aquaculture and Fisheries Biotechnology: Genetic Approaches (2nd Edition) - Dunham, Rex A (CABI, 2014)
Aquaculture is an ancient form of farming dating back 2000 years or more in China and to the Roman Empire (Balon, 1995; Dunham et al., 2001). However, only in the last few decades has aquaculture grown into a global practice resulting in tremendous worldwide production. Aquaculture pro- duction has enlarged dramatically since the early 1980s, and will become increasingly important as demand for ﬁ sh products increases, world harvest by capture ﬁ sher- ies reaches a plateau or declines and human population numbers expand. Aquaculture now accounts for 50% of global ﬁ sh con- sumption (FAO, 2009). The biomass of ﬁ sh that can be pro duced per surface area is much greater than that for terrestrial ani- mals, indicating that aquaculture could be the key for providing global food security.